Penerapan Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam - Nelly (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
As part of the post-pandemic recovery of online learning, the Ministry of Education and Culture officially launched a modern curriculum entitled